2020
DOI: 10.21037/apm-19-385
|View full text |Cite
|
Sign up to set email alerts
|

The application of thromboelastography in risk stratification for selective thromboembolism prophylaxis after total joint arthroplasty in Chinese: a randomized controlled trial

Abstract: Background: As Asian populations, Chinese have a lower rate of high-risk gene mutations in venous thrombosis. Therefore, individual patient risk assessment, rather than a "blanket policy", is considered the best thromboembolism prophylaxis for Chinese. The purpose of this study was to evaluate the effectiveness and safety of selective thromboembolism prophylaxis compared with conventional thromboembolism prophylaxis by risk stratification with thromboelastography (TEG) after joint arthroplasty in Chinese.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…Biased correlation analysis after controlling for age suggested that as testosterone decreased in men with diabetes, K values decreased and Angle, MA values, and CL values increased. Increased MA values suggested an increased risk of thrombosis, consistent with the results of previous studies ( Chen et al, 2020 ). Considering that reduced testosterone levels can lead to increased blood coagulation activity and inhibition of fibrinolytic activity, hypercoagulation occurs ( Si & Li, 2005 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Biased correlation analysis after controlling for age suggested that as testosterone decreased in men with diabetes, K values decreased and Angle, MA values, and CL values increased. Increased MA values suggested an increased risk of thrombosis, consistent with the results of previous studies ( Chen et al, 2020 ). Considering that reduced testosterone levels can lead to increased blood coagulation activity and inhibition of fibrinolytic activity, hypercoagulation occurs ( Si & Li, 2005 ).…”
Section: Discussionsupporting
confidence: 91%
“…Biased correlation analysis after controlling for age suggested that as testosterone decreased in men with diabetes, K values decreased and Angle, MA values, and CL values increased. Increased MA values suggested an increased risk of thrombosis, consistent with the results of previous studies (Chen et al, 2020).…”
Section: Thromboelastographysupporting
confidence: 91%
“…DEX can maintain a certain level of sedation, has the advantage of not causing respiratory depression, and is easy to awaken from[ 19 , 20 ]. DEX, which belongs to the imidazole derivative class, exerts its sedative effect by stimulating the alpha-2C receptor subtype, which synergizes with opioid drugs and reduces the required dose of opioid medications[ 21 , 22 ]. This drug has a relatively short duration of action, improves cardiovascular stability during surgery, and reduces the incidence of agitation.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to anticoagulation, TEG has been established to differentiate anticoagulated patients as well as monitor their therapy [ 60 - 62 ]. TEG-guided anticoagulation prophylaxis has better safety and comparable efficacy to conventional prophylaxis strategy [ 63 ]. TEG did not find any significance in detecting specific outcomes related to orthopedic surgery such as bone cement implantation syndrome and infections [ 64 , 65 ] (Table 5 ).…”
Section: Reviewmentioning
confidence: 99%